Hegemoni Adat Minangkabau dalam Novel “Tenggelamnya Kapal Van Der Wick” Karya Hamka - Ardianta, Shidiq (ESTETIK : Jurnal Bahasa Indonesia, 2024)
This article discusses the Minangkabau cultural hegemony portrayed in the novel "Tenggelamnya Kapal van der Wijck" by Hamka. In this literary work, the author delves deeply into how the cultural values and norms of Minangkabau influence the lives of the main characters. The concept of cultural hegemony takes center stage in analyzing the dynamics of social relationships, internal conflicts, and the characters' struggles to maintain their identities and personal values.Through a qualitative approach and textual analysis, this article explains how Minangkabau cultural hegemony plays a central role in determining the direction of the story and the conflicts that occur in the novel. This research also reveals how the main characters, such as Zainuddin and Hayati, interact with cultural hegemony in exploring the internal and external conflicts they face. The research findings indicate that Minangkabau cultural hegemony in the novel "Tenggelamnya Kapal van der Wijck" has a significant impact on character development and the plot. The conflict between traditional customs and individual desires adds a complex and profound dimension to understanding the characters